2015
DOI: 10.1093/gbe/evv192
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Adaptation to the Tibetan Plateau Inferred from Tibetan Loach Transcriptomes

Abstract: Triplophysa fishes are the primary component of the fish fauna on the Tibetan Plateau and are well adapted to the high-altitude environment. Despite the importance of Triplophysa fishes on the plateau, the genetic mechanisms of the adaptations of these fishes to this high-altitude environment remain poorly understood. In this study, we generated the transcriptome sequences for three Triplophysa fishes, that is, Triplophysa siluroides, Triplophysa scleroptera, and Triplophysa dalaica, and used these and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
65
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 68 publications
6
65
2
1
Order By: Relevance
“…The expression responses of GPI to divergent altitudes might be key in the adaptation of the energy metabolism of TP Gynaephora species. HIF1A is a main regulator in the hypoxia signaling pathway, and responses to hypoxia are largely regulated by changes in its expression in other animals (Wang et al., 2015; Xiao, 2015). Here, we observed significant expression changes in HIF1A along an altitudinal gradient, suggesting that the expression of this gene may be associated with adaptation to hypoxia in Gynaephora .…”
Section: Discussionmentioning
confidence: 99%
“…The expression responses of GPI to divergent altitudes might be key in the adaptation of the energy metabolism of TP Gynaephora species. HIF1A is a main regulator in the hypoxia signaling pathway, and responses to hypoxia are largely regulated by changes in its expression in other animals (Wang et al., 2015; Xiao, 2015). Here, we observed significant expression changes in HIF1A along an altitudinal gradient, suggesting that the expression of this gene may be associated with adaptation to hypoxia in Gynaephora .…”
Section: Discussionmentioning
confidence: 99%
“…Since the development of next-generation sequencing technology, RNA-seq has been widely used as an efficient and accessible approach to determine the evolutionary histories of non-model organisms when no genome information is available [28,29,30]. Here, we sequenced and assembled the transcriptomes of three closely related Misgurnus species, M. anguillicaudatus , M. bipartitus , and M. mohoity , to identify the genetic mechanisms in their adaptation to the temperature variations in their environments and provide valuable information for further studies to understand the genetic makeup of other fishes in thermal adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…If the p value was < 0.05, and a higher Ka/Ks (the ratio of nonsynonymous to synonymous Substitutions) value was obtained than the foreground branch than the background branches, the gene was considered to be a fast-evolving gene. To identify genes under positive selection, the branch-site model in the codeml program was used, with the null model assuming that all branches have been evolving at the same rate and the alternative model allowing foreground branch to evolve under a different rate [29,30]. As before, LRTs were used to discriminate between alternative models for each gene in the gene set, and p value was computed by comparing LRT to the χ 2 distribution, with the degree of freedom estimated as the difference of parameters between models.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, HIF1A is of relevance when fish colonize aquatic environments with differing oxygen regimens, for example benthic vs. limnetic habitats or different areas of the Baltic Sea. Rytkönen et al (2007) found no association between variation in the HIF1A coding region and adaptation to hypoxic conditions across various fish species, and markers linked to HIF1A do not appear be under directional selection among Baltic Sea stickleback populations ; however, the gene was recently found to be under positive selection in high-altitude loach lineages (Wang et al 2015). HIF1A is known to be transcriptionally regulated in fish (Liu et al 2013), and our identification of a trans-eQTL for HIF1A demonstrates that regulatory variation for this gene is present in Baltic Sea sticklebacks and could be an alternative, unexamined, target of selection.…”
Section: Discussionmentioning
confidence: 99%